Crosstalk between AdipoR1/AdipoR2 and Nrf2/HO‐1 signal pathways activated by β‐caryophyllene suppressed the compound 48/80 induced pseudo‐allergic reactions. (15th August 2021) - Pathak, Manash Pratim; Patowary, Pompy; Das, Aparoop; Goyary, Danswrang; Karmakar, Sanjeev; Bhutia, Yangchen D; Roy, Probin Kumar; Das, Sanghita; Chattopadhyay, Pronobesh
Abstract: Mast cell activation is initiated by two signalling pathways: immunoglobulin E (IgE)‐dependent and IgE‐independent pathway. It is reported that the IgE‐independent type or pseudo‐allergy pathway gets activated by G‐protein‐dependent activation of the mast cell. Recently, adiponectin (APN) receptors, AdipoR1, and AdipoR2 have been identified as G‐protein‐coupled receptors (GPCRs). Interestingly, APN replenishment is reported to activate the Nrf2/HO‐1 signalling axis. However, no study has been performed interlinking the role of APN and the Nrf2/HO‐1 signalling axis in pseudo‐allergic reaction. In the present study, we evaluated the anti‐pseudo‐allergic effects of β‐caryophyllene, an FDA‐approved food additive, in activating AdipoR1/AdipoR2 and Nrf2/HO‐1 axis signalling pathway. Compound 48/80 (C48/80)‐induced systemic and cutaneous anaphylaxis‐like shock in BALB/c mice was performed to assess the efficacy of β‐caryophyllene (BCP). To assess the effect of BCP in anaphylactic hypotension, mean arterial pressure was measured in Wistar rats. Inhibitory properties of BCP in mast cell degranulation were estimated in rat peritoneal mast cells (RPMCs). ELISA was performed to estimate interleukin (IL)‐6, tumour necrosis factor (TNF), IL‐1β, IgE, ovalbumin (OVA)‐IgE and APN and western blotting for protein expression of Nrf2/HO‐1 and AdipoR1‐AdipoR2. BCP dose‐dependently inhibited systemic and cutaneous anaphylaxis‐like shock induced by C48/80. BCP dose‐dependently inhibited the mast cell degranulation followed by inhibition of histamine release. Also BCP dose‐dependently activated the Nrf2/HO‐1 and AdipoR1‐AdipoR2 signalling axis pathway. Moreover, BCP reversed the drop in blood pressure when the haemodynamic parameters were accessed. Our findings suggest that BCP is a potent AdipoR1/AdipoR2‐Nrf2/HO‐1 axis pathway agonist that may suppress the IgE‐independent pathway towards allergic response to secretagogues.